Influence of anthropogenic factors on microhabitats inhabited by riverine hydrobionts - assessment with MRT method - Osadowski, Zbigniew; Obolewski, Krystian; Strzelczak, Agnieszka (Ecological Questions, 2008)
This study concerns the influence of urban area on vegetation and invertebrates inhabiting the Słupia River (northern Poland). Altogether, 10 plant communities and 37 macrozoobenthos taxa were determined during four seasonal samplings (October 2005, January, April and August 2006). In order to reveal how the city of Słupsk affects the vegetation and fauna, MRT (multivariate regression tree) models were created. On their basis the most important factors were determined from the following set of variables: season, water temperature, salinity, distance, water depth, bottom type, location in the river bed and degree of river bed transformations. Performed analyses showed that vegetation in the urban area was primarily influenced by distance (correlated with anthropogenic pressure), while for invertebrates season and temperature were the most important factors.